Pentingnya Transparansi Beneficial Ownership oleh Korporasi - Agustianto, Agustianto (JUSTISI, 2022)
The development of the business world in Indonesia in the current modern era creates a new legal phenomenon that needs attention. This legal phenomenon is the existence of crimes that are hidden within the corporation. Therefore, Indonesia implements beneficial owner transparency for all corporations. Â The purpose of this study is to analyze the application of beneficial owners in Indonesia. The method used in this research is normative juridical using the Theory of Law as a tool of social engineering by Roscoe Pound. Based on the results of the study, it was found that the implementation of BO transparency in Indonesian corporations had not gone well. Only 8.3% percent of companies in Indonesia report BO, even though Indonesia has regulated the obligation to report BO in Presidential Decree No. 13 of 2018. This shows that the laws made have not been able to manipulate and or change people's behavior.